SEJARAH DAN PERKEMBANGAN GEREJA KRISTEN PROTESTAN SIMALUNGUN RAYA USANG KECAMATAN DOLOG MASAGAL KABUPATEN SIMALUNGUN 1903-2023 - Ayu Lestari Sidauruk; Andres M. Ginting; Satria Chandra Chandra (Prodi Pendidikan Sejarah FKIP USI, 2026)
Based on the background of the establishment of the GKPS Raya Usang church, this church is one of the oldest churches in the GKPS congregation. The purpose of this study is to explain historically how the history and development of the GKPS church in Raya Usang. The method used by researchers in this writing is the Historical method. The results of the study show that the formation of the congregation and the establishment of the GKPS Raya Usang which is part of the Raya Usang Resort in Dolog Masagal District cannot be separated from the struggle carried out by the missionary August Theis and the evangelists along with all the figures who played a role in the establishment of this church including the spirit and unity of the village community of Raya Usang, by having the awareness to build a church building that should be separated from the school building. In its development, the GKPS Raya Usang church cannot be separated from the influence of the leadership of the congregation council who plays an active role in carrying out its duties and responsibilities through the